A coloured polyester fabric with antimicrobial properties conferred by copper nanoparticles. (10th October 2019) - Afshari, Sepideh; Montazer, Majid; Harifi, Tina; Mahmoudi Rad, Mahnaz
Abstract: In this study, we aimed to produce a coloured polyester fabric through the in situ sonosynthesis of copper nanoparticles using copper sulphate, hydrazine, sodium hydroxide and polyvinylpyrrolidone. The treated fabrics were characterised by X‐ray diffraction, field emission scanning electron microscopy, energy‐dispersive X‐ray spectroscopy and elemental mapping. Moreover, mechanical properties, wettability and antibacterial/antifungal activities of the treated fabrics were evaluated. Central composite design based on the response surface methodology was used to study the effect of copper sulphate, hydrazine hydrate and sodium hydroxide on the weight gain and colour of the treated fabrics. In addition to their roles as reducing agents, hydrazine and sodium hydroxide were responsible for the simultaneous aminolysis and hydrolysis of polyester, increasing the adsorption of nanoparticles on the surface. According to the results, the reddish brown samples treated with copper nanoparticles showed excellent antibacterial and antifungal efficiencies, improved tensile strength and decreased wettability.